A formação de educadores sociais que trabalham com a Educação não formal: a percepção de dois profissionais - Martins, Ana Paula (2014)
The present study aimed to understand how social educators who work with nonformal education realize their formation process. The research used a qualitative approach and data were collected through a reflective interview, as proposed by this dissertation advisor, Prof.ª Dr.ª Szymanski.This research took place at the Centro para Crianças e Adolescentes (CCA), in a community of Vila Brasilândia, located in the northern zone of São Paulo, which serves children and adolescents 06-14 years out of school time district, maintained by an organization non-profit. The study included two educators. Two meetings were held with each educator for the interview and feedback session. The data analysis was to reference the dialogic proposal of Paulo Freire about the significant elements that permeate the universe of non-formal education and training of social educators process. The results showed that social educators understand that their training is in daily tasks, because they had no training or initial training to carry out such activity.This research pointed to the fragility of this profession, a broad and complex field that requires higher penetrations discussions, social reflections on their professional role and functions in social education. It is emphasized at the end of this study, the establishment of training courses and improvement paths as facilitators for the support and development of childcare work